The in cellular and in vivo melanogenesis inhibitory activity of safflospermidines from Helianthus annuus L. bee pollen in B16F10 murine melanoma cells and zebrafish embryos - Phanthiwa Khongkarat; Wannakarn Kitipaspallop; Songchan Puthong; Wittaya Pimtong; Preecha Phuwapraisirisan; Chanpen Chanchao (PLoS ONE, 2025)
Melanin, synthesized by tyrosinase (TYR), is a natural pigment essential for skin protection and pigmentation. However, excessive melanin production can cause dermatological disorders. Safflospermidines, comprised of safflospermidine A and B isomers isolated from sunflower (Helianthus annuus L.) bee pollen, were shown to exhibit a strong in vitro TYR inhibitory activity against mushroom TYR. However, their anti-melanogenesis activity in cellular and in vivo models remains unexplored. This study firstly evaluated the effects of these safflospermidines on melanogenesis in α-melanocyte stimulating hormone-stimulated B16F10 cells, using kojic acid as a positive control. Cytotoxicity was evaluated using the MTT assay, while TYR activity and melanin content were measured to assess melanogenesis inhibition. The expression of key melanogenesis-related genes was analyzed through quantitative real-time reverse transcription (RT-q)PCR to elucidate the molecular mechanisms involved. Secondly, the melanogenic activity and potential toxicity of the compounds were confirmed in zebrafish embryos, with phenylthiourea (PTU) as a reference. The results revealed that a mixture of these two safflospermidines exhibited no cytotoxicity across the treated concentration range (0–500 µg/mL). At 62.5 µg/mL, safflospermidines significantly reduced the intracellular melanin content by 21.78 ± 4.01% and the TYR activity by 25.71 ± 3.08% in B16F10 cells through downregulation of TYR, TYR-related protein 1 (TRP-1), and TRP-2 gene expression. Additionally, the safflospermidines induced a noticeable reduction in dendritic cell structures, which likely contributed to the marked decrease in extracellular melanin levels. Kojic acid (250 μg/mL) significantly reduced the melanin content and TYR activity by suppressing all three melanogenesis-related genes. In zebrafish embryos, safflospermidines showed no toxicity or morphological abnormalities within a concentration range of 0–62.5 µg/mL, and at a concentration of 15.63 µg/mL the melanin production in zebrafish embryos was significantly reduced by 28.43 ± 9.17%. In comparison, 0.0015% (v/v) PTU decreased melanin production by 53.20 ± 3.75%. These findings suggest that safflospermidines are safe, effective melanin inhibitors with potential applications in pharmaceuticals and cosmetics for managing hyperpigmentation.